The effect of polyol types and molecular weight on the shape memory properties of palm kernel oil - Based polyurethane - Trinh N.H.; Rasli N.A.; Jaafar M.; Ali E.S.; Zain N.M.; Viet C.X.; Zubir S.A. (Elsevier Ltd, 2024)
Indexed by WOS/Scopus/ERA